2015
DOI: 10.1088/0004-637x/811/2/117
|View full text |Cite
|
Sign up to set email alerts
|

Search for Precursor Eruptions Among Type Iib Supernovae

Abstract: The progenitor stars of several Type IIb supernovae (SNe) show indications of extended hydrogen envelopes. These envelopes might be the outcome of luminous energetic pre-explosion events, so-called precursor eruptions. We use the Palomar Transient Factory (PTF) pre-explosion observations of a sample of 27 nearby SNe IIb to look for such precursors during the final years prior to the SN explosion. No precursors are found when combining the observations in 15-day bins, and we calculate the absolute-magnitude-dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 62 publications
7
63
0
Order By: Relevance
“…The flux at the position of PTF12os in this preexplosion image cannot have been dominated by a single massive SN progenitor. In the precursor study by Strotjohann et al (2015), it was also found that the source located at the position of PTF12os is still at approximately the same brightness 3 years after the SN occurred.…”
Section: Ptf12osmentioning
confidence: 92%
“…The flux at the position of PTF12os in this preexplosion image cannot have been dominated by a single massive SN progenitor. In the precursor study by Strotjohann et al (2015), it was also found that the source located at the position of PTF12os is still at approximately the same brightness 3 years after the SN occurred.…”
Section: Ptf12osmentioning
confidence: 92%
“…Evidence for significantly enhanced mass loss timed with the explosion has been found for the H-poor progenitors of both type-IIb SNe (GalYam et al 2014;Kamble et al 2015;Maeda et al 2015) and type-Ib SNe (Svirski & Nakar 2014), as well as for the H-and He-poor progenitors of type-Ic SNe associated with some nearby gamma-ray bursts (Margutti et al 2015;Nakar 2015). Along the same line, it is relevant to mention the possible detection of an outburst from the progenitor of the broad-line type-Ic SN PTF11qcj ∼2.5 years before stellar death (Corsi et al 2014), a possible precursor in the type-IIb SN 2012cs (Strotjohann et al 2015), and the recent detection of interaction of the H-poor superluminous SN iPTF13ehe with H-rich material at late times (Yan et al 2015), as well the evidence for significant temporal variability in the radio lightcurves of Ib/c SNe (Soderberg 2007;Wellons et al 2012), which suggests significant structure in their circumstellar media (CSM).…”
Section: Introductionmentioning
confidence: 91%
“…This bonanza of physical puzzles is closely linked with compact object formation by corecollapse supernovae (e.g., Eldridge and Tout, 2004;Özel et al, 2010;Perego et al, 2015;Sukhbold et al, 2016;Suwa et al, 2015;Timmes et al, 1996) and the diversity of observed massive star transients (e.g., Ofek et al, 2014;Smith et al, 2016;Van Dyk et al, 2000). Recent observational clues that challenge conventional wisdom (Boggs et al, 2015;Jerkstrand et al, 2015;Strotjohann et al, 2015;Vreeswijk et al, 2014;Zavagno et al, 2010), coupled with the expectation of large quantities of data from upcoming surveys (e.g., Creevey et al, 2015;Papadopoulos et al, 2015;Sacco et al, 2015;Yuan et al, 2015), new measurements of key nuclear reaction rates and techniques for assessing reaction rate uncertainties Wiescher et al, 2012), and advances in 3D pre-SN modeling (Couch et al, 2015;Jones et al, 2017;Müller et al, 2016), offer significant improvements in our quantitative understanding of the end states of massive stars.…”
Section: B Helium Burning In Massive Starsmentioning
confidence: 99%